Application of moderate hypothermia while performance of the aortal arch reconstruction in new-born babies in conditions of selective antegrade cerebral perfusion - Ya. P. Truba; R. І. Sekelyk; І. V. Dzyurii; O. S. Golovenko; V. V. Lazoryshynets (Клінічна хірургія, 2020)
Objective. To estimate a security of application of moderate hypothermia while performing the aortal arch reconstruction in new-born babies in conditions of selective antegrade cerebral perfusion.